2007
DOI: 10.4049/jimmunol.179.7.4598
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Negatively Regulates TLR-Mediated Activation Pathways

Abstract: In innate immunity, microbial components stimulate macrophages to produce antimicrobial substances, cytokines, other proinflammatory mediators, and IFNs via TLRs, which trigger signaling pathways activating NF-κB, MAPKs, and IFN response factors. We show in this study that, in contrast to its activating role in T cells, in macrophages the protein phosphatase calcineurin negatively regulates NF-κB, MAPKs, and IFN response factor activation by inhibiting the TLR-mediated signaling pathways. Evidence for this nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 61 publications
4
102
1
Order By: Relevance
“…5C). In myeloid cells, calcineurin activation without NF-kB recruitment by ITAM-coupled receptors was shown to inhibit TLR activation (29,30). Thus, a similar mechanism could play a role in BCR-mediated control of the LPS responsiveness in developing B cells, where the acute signal from the BCR, an ITAM-associated receptor, seems to inhibit TLR4 signaling through a calcineurindependent way.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…5C). In myeloid cells, calcineurin activation without NF-kB recruitment by ITAM-coupled receptors was shown to inhibit TLR activation (29,30). Thus, a similar mechanism could play a role in BCR-mediated control of the LPS responsiveness in developing B cells, where the acute signal from the BCR, an ITAM-associated receptor, seems to inhibit TLR4 signaling through a calcineurindependent way.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we could not distinguish whether the decrease of CD23 + B cells upon BCR ligation was mainly due to induction of (29,30). As BCR is associated with ITAM-bearing molecules, we next asked whether a similar mechanism could play a role in BCRmediated regulation of LPS responsiveness in developing B lymphocytes.…”
Section: Lps Does Not Depend On Induction Of Secondary Factors To Genmentioning
confidence: 99%
“…PKC␦ has been shown recently to bind to a TLR signaling complex, namely TIRAP/Mal, and thus participate in TLR signaling (44). In addition, Kang et al showed a role of the phosphatase calcineurin in regulating TLR-activated pathways (30). Interestingly, all of these mediators are also believed to be key mediators in the development of LV remodeling (14).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, such intracellular mediators have been shown to be involved in TLR signaling and regulation (29,30). To investigate whether or not these mediators are modulated by TLR4 after MI, we measured its cardiac protein activation.…”
Section: Cardiac Protein Activation Of Pkc␦ P42/44 Jnk and Calcinementioning
confidence: 99%
“…Recently, it was reported that FK506 activates nuclear factor (NF)-kB and tumour necrosis factor (TNF)-a expression in macrophages, and this effect was shown to be through its inhibition of CN activity [25]. This suggests that innate immune responses may be up-regulated in Cnab -/-and DKO mice leading to increased proinflammatory cytokine production such as TNF-a, which can contribute to early lethality of DKO mice.…”
Section: Tgfb1mentioning
confidence: 99%